META-ANALYSIS: THE EFFECT OF THE SCIENCE, TECHNOLOGY, AND SOCIETY LEARNING MODEL ON STUDENTS HIGH ORDER THINKING SKILLS - R Rikizaputra; F Festiyed; A Asrizal; Skunda Diliarosta (Jurnal Pelita Pendidikan, 2021)
This study aims to analyze the effect of the science, technology, and society (STS) learning model on students' higher-order thinking skills (HOTS) in science subjects. This influence is viewed from several aspects, namely aspects of higher-order thinking skills, education level, and dimensions of science studies. This influence is seen from the effect size (ES) in each article. This research uses the meta-analysis method of 20 (twenty) scientific articles from journals. The results of this study indicate that the STS learning model has a good effect on students' higher-order thinking skills (HOTS) in science learning. Aspects of high-order thinking skills critical thinking have the highest average effect size (ES), namely 1,84. Students at the high school level experienced higher order thinking skills development which was better than students at the junior and elementary school levels with an average ES of 1,77. The dimensions of the Biology Science study show a better effect if it is taught with the community technology science (STS) model with an average effect size (ES) of 1,70.